Rhythm and Tempo: A Study in Music History - Sachs, Curt 1881-1959 (New York Norton, 1953)
This is the first book to trace the history of rhythm and tempo in its entirety. The author brings to this study a vast knowledge of the musical lore of all cultures, East & West, from the most distant past to the present. There are more than 200 musical examples included ranging from the native songs of Asian & African jungles to rumba, jazz, and Stravinsky.
Keywords: Past; Music history; Tempo; Rhythm